1993
DOI: 10.1002/jts.2490060105
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of intrusive cognition in PTSD: Use of the modified Stroop paradigm

Abstract: I n this article, we review research supporting the modified

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(51 citation statements)
references
References 12 publications
1
48
0
1
Order By: Relevance
“…'body-bag') relative to several categories of control words. Delayed color-naming for trauma-related words was found in several samples of PTSD-patients, including Vietnam veterans (McNally et al, 1993), rape victims (Foa et al, 1991), and motor vehicle accident survivors (Bryant and Harvey, 1997). Since delays in color-naming are involuntary, this indicates that PTSDpatients have an automatic attentional bias to trauma words.…”
Section: Automatic Processing Of Trauma-related Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…'body-bag') relative to several categories of control words. Delayed color-naming for trauma-related words was found in several samples of PTSD-patients, including Vietnam veterans (McNally et al, 1993), rape victims (Foa et al, 1991), and motor vehicle accident survivors (Bryant and Harvey, 1997). Since delays in color-naming are involuntary, this indicates that PTSDpatients have an automatic attentional bias to trauma words.…”
Section: Automatic Processing Of Trauma-related Informationmentioning
confidence: 99%
“…Accordingly, PFC dysfunction may also play a role in the interference on Stroop-tasks (e.g. McNally et al, 1990McNally et al, , 1993 and lack of inhibition (Vasterling et al, 1998) of PTSD-patients.…”
Section: The Prefrontal Cortexmentioning
confidence: 99%
“…Mismatch between the color and content of the word (e.g., the word "green" printed in red) typically results in a longer response latency, which has been typically regarded as evidence of cognitive interference. Modified versions of Stroop tests presenting emotional threat words have been used to examine attentional biases in numerous conditions, including depression (Klieger & Cordner, 1990;Segal, Truchon, Gemar, & Guirguis, 1995;Segal & Vella, 1990), panic disorder (McNally et al, 1994;McNally, Riemann, & Kim, 1990;McNally, Riemann, Louro, Lukach, & Kim, 1992), obsessive-compulsive disorder (Foa, Ilai, McCarthy, Shoyer, & Murdock, 1993;Lavy, Vanoppen, & Vandenhout, 1994), posttraumatic stress disorder (Foa, Feske, Murdock, Kozak, & Mccarthy, 1991;Kaspi, McNally, & Amir, 1995;McNally, English, & Lipke, 1993), specific phobia (Lavy, Vandenhout, & Arntz, 1993;Mathews & Sebastian, 1993), and SAD (Becker, Rinck, Margraf, & Roth, 2001;Hope, Rapee, Heimberg, & Dombeck, 1990;Lundh & Ost, 1996;Maidenberg, Chen, Craske, Bohn, & Bystritsky, 1996;Mattia, Heimberg, & Hope, 1993;McNeil et al, 1995;Spector, response latencies to threat words in contrast with non-threat words have been deemed to indicate selective attention towards the threat.…”
Section: Emotional Stroop Testmentioning
confidence: 99%
“…Previous studies whose researchers used such methods have shown patients with PTSD to be characterized by informationprocessing biases that may be related to intrusive cognitive symptoms. First, an attentional bias favoring the processing of trauma-related information has been repeatedly demonstrated in patients with PTSD but not in controls (e.g., Bryant & Harvey, 1995;Foa, Feske, Murdock, Kozak, & McCarthy, 1991;Kaspi, McNally, & Amir, 1995;McNally, English, & Lipke, 1993;McNally et al, 1987;Thrasher, Dalgleish, & Yule, 1994). For example, Bryant and Harvey ( 1995 ) compared the performance of individuals involved in motor vehicle accidents with PTSD, simple phobia of driving, or low anxiety on an emotional Stroop color-naming paradigm.…”
Section: Cognitive Effects Of Alcohol In Ptsdmentioning
confidence: 99%
“…Some clinical researchers have also advocated the use of cognitive psychology paradigms, such as the emotional Stroop task, as additional clinical assessment tools (e.g., McNally et al, 1993). There are several interviews available for diagnosing PTSD (for a review, see Blake et al, 1995).…”
Section: Assessmentmentioning
confidence: 99%